The formation mechanism of “sports fandom circle” in the digital media era: An analysis from the perspective of fan emotional dynamic development - Yuan Cheng; Yin Wu (PLoS ONE, 2025)
The rise of the “sports fandom circle” has become a significant phenomenon in the digital media era, reshaping the emotional and social dynamics of sports fan communities. This study employs grounded theory methodology to analyze web-scraped data from 40 selected accounts on major Chinese social media platforms [Weibo, Xiaohongshu, and Bilibili] over a two-year period. These accounts were identified based on their focus on celebrity athletes [e.g., Fan Zhendong, Sun Yingsha, Wang Chuqin] and their engagement in fan-specific activities such as support, fan clubs, and voting. The analysis involved open coding, axial coding, and selective coding to construct an emotional interaction model. Our findings reveal that international sports events serve as emotional catalysts, where competition, nationalism, and athlete narratives trigger fans’ emotional arousal. Digital media platforms, including spatiotemporal extension, virtualization, and selectivity, amplify these emotions, fostering proximal emotional attachment to athletes. Through symbolic interactions and digital consumption, fans transition from individual engagement to collective emotional aggregation, solidifying their sense of group identity. However, in the reproduction process, the anonymity of digital media platforms can lead to emotional polarization, intensifying conflicts among fan groups, or facilitate emotional resocialization, fostering more rational and inclusive fandom behaviors. This study provides a theoretical framework for understanding the emotional evolution of sports fandom in the digital media era and offers practical insights for managing online fan communities, mitigating conflicts, and promoting a healthier digital sports culture.